Nanotechnology : From Nanostructures to System - Anon (Universiti Malaysia Perlis, 2012)
Profesorial Lecture Series - Nanotechnology: Nanostructures to System organized by Institute of Nano Electronic Engineering (INEE), 13th December 2011 at Kapitol Hall, Kangar, Perlis, Malaysia.